POSTMODERNISME : Sebuah Arus di dalam Zaman Kita - Moa, Antonius (LOGOS, 2005)
Postmodernism is a popular usage terminology in our life. In fact this term has been used in all aspects of life with different meanings. Sometimes the usage makes the term itself blurred and even contradictory to the term. Though it some time makes us confused, it can not to denied that postmodernism has become a fact in our era. It has become a “trend” among many streams. As a trend, postmodernism has contributed a special characteristic to the generation of our era.